2022
DOI: 10.1038/s41467-022-31622-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide signatures of synergistic epistasis during parallel adaptation in a Baltic Sea copepod

Abstract: The role of epistasis in driving adaptation has remained an unresolved problem dating back to the Evolutionary Synthesis. In particular, whether epistatic interactions among genes could promote parallel evolution remains unexplored. To address this problem, we employ an Evolve and Resequence (E&R) experiment, using the copepod Eurytemora affinis, to elucidate the evolutionary genomic response to rapid salinity decline. Rapid declines in coastal salinity at high latitudes are a predicted consequence of glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(62 citation statements)
references
References 126 publications
1
60
1
Order By: Relevance
“…Experimental evolution studies also revealed NHA paralogs as genetic targets of selection during rapid salinity decline in the laboratory (Stern et al, 2022). Of the NHA paralogs, the E. affinis paralogs NHA7 and NHA5 showed evolutionary shifts in gene expression between ancestral saline and recently derived freshwater populations, supporting the importance of NHA function during rapid salinity transitions (Posavi et al, 2020;Lee, 2021).…”
Section: Support For Model 1 In Crustaceansmentioning
confidence: 84%
See 3 more Smart Citations
“…Experimental evolution studies also revealed NHA paralogs as genetic targets of selection during rapid salinity decline in the laboratory (Stern et al, 2022). Of the NHA paralogs, the E. affinis paralogs NHA7 and NHA5 showed evolutionary shifts in gene expression between ancestral saline and recently derived freshwater populations, supporting the importance of NHA function during rapid salinity transitions (Posavi et al, 2020;Lee, 2021).…”
Section: Support For Model 1 In Crustaceansmentioning
confidence: 84%
“…Frontiers in Physiology frontiersin.org implicating NHA paralogs in freshwater adaptation (Posavi et al, 2020;Stern and Lee, 2020;Stern et al, 2022). Single-cell RNA sequencing could greatly improve our knowledge on the diverse ionocyte subtypes in fish and would potentially help identify new Na + uptake pathways in specific cell types (Leguen et al, 2015;Xue et al, 2015).…”
Section: Concluding Remarks On Na + Uptake In Aquatic Organismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diatoms exhibit high levels of inter- and intraspecific variation in gene expression in response to reduced salinity (Nakov et al 2020; Pinseel et al 2022), providing numerous targets for natural selection to optimize gene expression for a particular salinity environment (López-Maury et al 2008; Bedford and Hartl 2009; Gomez-Mestre and Jovani 2013). Finally, differences in codon usage (Prabha et al 2017), nucleotide substitution rates (Mitterboeck et al 2016), transposable element activity (Yuan et al 2018), epigenetic responses (Artemov et al 2017), and epistatic interactions (Stern et al 2022) have been implicated in adaptation to freshwaters in other groups. The genomic resources and phylogenetic framework presented here represent an important advance towards identifying the genes and evolutionary processes underpinning freshwater adaptation by diatoms.…”
Section: Discussionmentioning
confidence: 99%